PENGARUH FAKTOR DEMOGRAFI TERHADAP PENGETAHUAN WAJIB PAJAK NON KARYAWAN DI INDONESIA - Muhammad Destyawan; Amir Hidayatulloh (Universitas Multimedia Nusantara, 2022)
Abstract— The Purpose of this study is to analyze the demographic factors that influence tax knowledge. The Population in this study is individual taxpayers in Indonesia. The sampling technique in this study uses purposive sampling, with criteria (1) individual non-employee taxpayers in Indonesia, and (2) having a taxpayer base number. Data collection in this study used a questionnaire with help of Google Form. Respondents in this study numbered 71 respondents who were dominated by male respondents (51 respondents), aged 25-34 years (35 respondents). Data analysis techniques in this study used multiple linear regression analysis with the help of SPSS tools. This study found that demographic factors that influenced tax knowledge were education level and income level. However, age and gender do not affect tax knowledge. Keywords: Tax Knowledge, Age, Gender, Education Level, Income Level, Demographic Factors